2009
DOI: 10.1002/marc.200800591
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of Collagen‐Like Peptides in vitro Provides Structural Causes of Osteogenesis Imperfecta

Abstract: Collagen type I peptides, representative of native to disease states for the bone disease, Osteogenesis imperfecta, were studied with regard to self-assembly into triple helices and liquid crystalline mesophases. The purpose of the study was to establish insight into collagen mutations in terms of propagation of single chain defects up the scale of materials hierarchy, toward solid state fibril assemblies formed from collagen. Studies carried out in vitro demonstrated the value of this approach in establishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In addition, the peak at about 1685 cm −1 suggests the occurrence of turns in the secondary structure of the peptides. Further, the bands were observed in the region of 1618-1623 cm −1 , which confirms the presence of intermolecular aggregates [64][65][66]. The FT-IR analysis results corroborate with the circular dichroic secondary structural analysis.…”
Section: Peptidesupporting
confidence: 90%
“…In addition, the peak at about 1685 cm −1 suggests the occurrence of turns in the secondary structure of the peptides. Further, the bands were observed in the region of 1618-1623 cm −1 , which confirms the presence of intermolecular aggregates [64][65][66]. The FT-IR analysis results corroborate with the circular dichroic secondary structural analysis.…”
Section: Peptidesupporting
confidence: 90%
“…It is indicated that judicious molecular design can be used to control the morphology of self-assembly and the alignment of the resulting fibers. It should also be noted that the LLC formation by self-assembly of synthetic double-helix-forming molecules ,, has not been previously reported, and the results are reminiscent of the property of biological double-helical molecules and polymers such as DNA and RNA, polysaccharides, and actin , that form LLCs in aqueous media.…”
Section: Resultsmentioning
confidence: 97%
“…This is in contrast to acyclic systems, for example, ( M )-D- 4 /( P )-D- 5 , which forms gels composed of randomly oriented fibers. This is a notable LLC formed by the self-assembly of synthetic double helix organic molecules. , (2) The self-assembled system showed dynamic and reversible polymorphism between two ordered structures, the LLC and a turbid gel composed of randomly oriented bundles, attributed to a temperature change in a closed system (Figure d,e). The results are reminiscent of the self-assembly property and the dynamic and reversible polymorphism of actin, which play important roles in biological systems.…”
Section: Introductionmentioning
confidence: 99%